2015
DOI: 10.1007/s10926-015-9574-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modified Hatha Yoga in Industrial Rehabilitation on Physical Fitness and Stress of Injured Workers

Abstract: An 8-week modified hatha yoga training experience exerted therapeutic effects on physical fitness variables including flexibility of lower back and hamstrings, hand grip strength and vital capacity, but not on stress level in injured workers. These findings indicate that hatha yoga can be a beneficial adjunct to routine physical therapy treatment in industrial rehabilitation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Recently, Rachiwong et al demonstrated an improvement in physical fitness parameters after 8 weeks of a modified hatha yoga training intervention in the injured workers. These improvements support the notion that the practice of hatha yoga may adjunct to routine physical therapy treatment in rehabilitation programs 13 ) . In addition, Uebelacker et al.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Recently, Rachiwong et al demonstrated an improvement in physical fitness parameters after 8 weeks of a modified hatha yoga training intervention in the injured workers. These improvements support the notion that the practice of hatha yoga may adjunct to routine physical therapy treatment in rehabilitation programs 13 ) . In addition, Uebelacker et al.…”
Section: Introductionsupporting
confidence: 69%
“… ). The details of the modified hatha yoga training program have been described in a previous study 13 ) . The routine was practiced as a group following a DVD recording and conducted by instructors in a silent room.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Unfortunately this was a pre-post design with no control group. In a Hatha yoga study on flexibility, Hatha yoga was combined with physical therapy and compared to a physical therapy alone control group [25]. Following eight weeks of three 1-h sessions per week flexibility of the lower back and the hamstrings, hand grip strength and vital capacity were greater in the yoga plus physical therapy group.…”
Section: Physical Flexibilitymentioning
confidence: 99%
“…Yoga has been included as a component of exercises prescribed for many pulmonary rehabilitation programs [12] . It has also been included as an adjunct to physical therapy treatment in industrial rehabilitation programs and proven to enhance mind-body coordination [13] . Studies of short-term yoga practices have reported improved lung function parameters [14] , increased diffusion capacity [15] , decreased dyspnea-related distress [16] , and improved health-related quality of life [17] .…”
Section: Introductionmentioning
confidence: 99%